2019
DOI: 10.21511/imfi.16(2).2019.01
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of fiscal policy behavior in Nigeria

Abstract: The study investigated the factors that determine fiscal behavior in Nigeria. The vulnerability of fiscal policy framework in Nigeria to different shocks and the attendant effects on the behavior of fiscal policy are parts of the reasons that prompted this research work. Annual data between 1980 and 2015 on core fiscal variables such as government revenue, government expenditure, fiscal balance, public debt, as well as other variables such as oil price, exchange rate, and inflation rate commodity price among o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…The findings showed that financing of FMCHP was insufficient and unpredictable. Consistent with experiences in Senegal [16], the level of promised funds remained unchanged since inception despite increases in population of target beneficiaries and changes in the unit cost of services and drugs due to rising inflation rates [33]. Changes in target population and increase in inflation rates imply underfunding of the scheme even if government transferred fully the existing budget commitment to the programme.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The findings showed that financing of FMCHP was insufficient and unpredictable. Consistent with experiences in Senegal [16], the level of promised funds remained unchanged since inception despite increases in population of target beneficiaries and changes in the unit cost of services and drugs due to rising inflation rates [33]. Changes in target population and increase in inflation rates imply underfunding of the scheme even if government transferred fully the existing budget commitment to the programme.…”
Section: Discussionmentioning
confidence: 70%
“…Changes in target population and increase in inflation rates imply underfunding of the scheme even if government transferred fully the existing budget commitment to the programme. Inflation rate affects fiscal policy behaviour in Nigeria [33], and may explain the weak compliance with contribution rules by SLG. Besides evidence of state governments’ defaulting in their contributions to UHC schemes in Nigeria and Mexico [1719], other studies also found poor government commitment to funding UHC schemes consistent with findings of this study [15, 19].…”
Section: Discussionmentioning
confidence: 99%